2003
DOI: 10.1128/mcb.23.21.7698-7707.2003
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans EVL-14/PDS-5 and SCC-3 Are Essential for Sister Chromatid Cohesion in Meiosis and Mitosis

Abstract: Sister chromatid cohesion is fundamental for the faithful transmission of chromosomes during both meiosis and mitosis. Proteins involved in this process are highly conserved from yeasts to humans. In screenings for sterile animals with abnormal vulval morphology, mutations in the Caenorhabditis elegans evl-14 and scc-3 genes were isolated. Defects in cell divisions were observed in germ line as well as in vulval and somatic gonad lineages. Through positional cloning of these genes, we have shown that EVL-14 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 47 publications
4
56
2
1
Order By: Relevance
“…Pds5A is a cohesin complex-interacting protein, which is involved in the establishment, maintenance and dissolution of sister chromatid cohesion (27)(28)(29)(30)34,35). Although details about its function remain unresolved, it could also play a role in tumorigenesis (25,26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pds5A is a cohesin complex-interacting protein, which is involved in the establishment, maintenance and dissolution of sister chromatid cohesion (27)(28)(29)(30)34,35). Although details about its function remain unresolved, it could also play a role in tumorigenesis (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…In fission yeast and vertebrate cells, separase plays a less important role in sister chromatid separation and it is thought that other mechanisms could regulate chromatid segregation in these cell types (30). It has been shown that Pds5 could be involved in the establishment, maintenance and dissolution of cohesion in both yeasts and humans (27)(28)(29)(30)34,35). It could also be implicated in embryonic development (36).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cohesion complex proteins present in the nuclear matrix are involved in chromosome organization and the establishment of chromosome boundaries. The cohesion protein SCC3 was first identified as a member of the yeast mitotic cohesin complex (Toth et al, 1999) and was subsequently identified in Caenorhabditis elegans and Arabidopsis (Pasierbek et al, 2003;Wang et al, 2003).This SCC3 protein (spot no.4) was identified in our study shows 12% amino acid sequence homology with Arabidopsis. In Arabidopsis, SCC3 protein expressed in roots, mature leaves and is mainly involved in both meiotic and mitotic divisions.…”
Section: Sister Chromatid Cohesion Protein 3 (Scc3)mentioning
confidence: 70%
“…In yeast only Scc1 is replaced by meiosis-specific Rec8 (Klein et al 1999, Watanabe & Nurse 1999, whereas in mammalian meiosis two additional replacements occur: Smc1 by Smc1b, and STAG3 for SA1/SA2 (Prieto et al 2001, Revenkova et al 2001. While single candidates where found for SCC-3 (Wang et al 2003) and the two subunits belonging to the structural maintenance of chromosomes (SMC) family , Chan et al 2003, SMC-1 (or HIM-1) and SMC-3, REC-8 is one of the four Rad21/Scc1/Rec8 homologs present in C. elegans genome (Pasierbek et al 2001). REC-8 localizes at chromosomal axes throughout meiosis I, and depletion causes embryonic lethality, a strong Him phenotype and cytological defects associated with defective synapsis and premature separation of sister chromatids prior to the first meiotic division.…”
Section: From Mitosis To Meiosismentioning
confidence: 99%